The Assessment of Chinese Children’s English Vocabulary—A Culturally Appropriate Receptive Vocabulary Test for Young Chinese Learners of English - de Ruiter, Laura E.; Wen, Peizhi; Chen, Si (Frontiers in Psychology, 2022)
Millions of Chinese children learn English at increasingly younger ages. Yet when it comes to measuring proficiency, educators, and researchers rely on assessments that have been developed for L1 learners and/or for different cultural contexts, or on non-validated, individually designed tests. We developed the Assessment of Chinese Children’s English Vocabulary test (ACCE-V) to address the need for a validated, culturally appropriate receptive vocabulary test, designed specifically for young Chinese learners. The items are drawn from current teaching materials used in China, and the depictions of people and objects are culturally appropriate. We evaluated the instrument’s reliability and validity in two field tests with a combined sample size of 1092 children (181 children for the first field test and 911 children for the second field test, age range from 3;1 to 7;7, mean age: 5;2. Item Response Theory (IRT) analyses show that the ACCE-V is sufficiently sensitive to capture different proficiency levels and that it has good psychometric properties. ACCE-V scores were correlated with Peabody Picture Vocabulary Test scores, indicating concurrent validity. We found that children’s age and English learning experience can significantly predict the scores of ACCE-V, but the effect of English learning experience is greater. The ACCE-V thus offers an alternative to existing vocabulary tests. We argue that culturally appropriate assessments like the ACCE-V are fairer to learners and help promote an English learning and teaching environment that is less dominated by Western cultures and native speaker norms.